2016
DOI: 10.1021/acs.energyfuels.6b01658
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Vapor Condensation on Heat Exchanging Surfaces: Laboratory-Scale Experiments and a Mechanistic CFD Modeling Approach

Abstract: Inorganic vapors and their condensation can lead to severe operational problems in pulverized fuel systems such as integrated gasification and combined-cycle power plants or a conventional pulverized fuel combustion system. In order to understand these phenomena, a laboratory-scale cooling line for hot gases is used to measure and quantify the deposition of alkali vapors caused by heterogeneous condensation on a horizontal probe. The cooling line consists of two zones, an isothermal evaporation zone for the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“… 5,6 These inorganic vapors deposited on the heating surface and fly ash particles via condensation, thermophoresis and chemical reactions. 7–9 For instance, Li et al 10 systematically investigated the characteristics of ash deposits formed on an air-cooled steel probe simulating superheater surfaces at different temperatures. They reported that fine ash rich in Na, Ca, S, and Mg on the probe was responsible for the severe ash deposition.…”
Section: Introductionmentioning
confidence: 99%
“… 5,6 These inorganic vapors deposited on the heating surface and fly ash particles via condensation, thermophoresis and chemical reactions. 7–9 For instance, Li et al 10 systematically investigated the characteristics of ash deposits formed on an air-cooled steel probe simulating superheater surfaces at different temperatures. They reported that fine ash rich in Na, Ca, S, and Mg on the probe was responsible for the severe ash deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the deposit layer causes deteriorated heat transfer, which in turn reduces the steam production efficiency of power stations. The main mechanisms leading to the formation of deposit layers on superheater tubes are inertial impaction, thermophoresis of small particles due to a temperature gradient, diffusion of aerosols, heterogeneous condensation of inorganic vapors, and chemical reactions of such vapors with the deposit . Due to the lower content of vaporized inorganics during coal combustion, deposit build-up takes usually longer when compared to the combustion of straw or other high-alkali biomass materials …”
Section: Introductionmentioning
confidence: 99%
“…The main mechanisms leading to the formation of deposit layers on superheater tubes are inertial impaction, thermophoresis of small particles due to a temperature gradient, diffusion of aerosols, heterogeneous condensation of inorganic vapors, and chemical reactions of such vapors with the deposit. 21 Due to the lower content of vaporized inorganics during coal combustion, deposit build-up takes usually longer when compared to the combustion of straw or other high-alkali biomass materials. 22 In a pilot-scale study, Nielsen et al 17 showed that the initial deposits formed during pure straw combustion are mainly composed of condensed KCl and K 2 SO 4 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…The formation of a sticky layer, coming from condensed vapors, is expected to be crucial for particle deposition in the early stage. 41 Normally, three types of condensation were proposed: 42 (1) directly condensing on the heating exchanging surfacecalled direct condensation, (2) condensing on the particle surface called heterogeneous condensation, and (3) form new aerosol particlescalled nucleation. In this work, nucleation condensation is neglected because of the high furnace temperature.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…21,22 The saturation vapor pressure of the condensing species in eq 4 may be calculated via eq 7. 42 Coefficients A 0 , B 0 , C 0 for varied sodium species are obtained from Kleinhans's work. 42…”
Section: Energy and Fuelsmentioning
confidence: 99%